2008
DOI: 10.2478/v10109-009-0005-z
|View full text |Cite
|
Sign up to set email alerts
|

The methods of physiotherapy, which are used by children with Down syndrome and congenital heart disease which require cardiosurgical intervention

Abstract: Wprowadzenie Zespół Downa (ZD) jest najczęściej występującą jednostką chorobową o podłożu genetycznym [1]. Stanowi naczelną przyczynę umiarkowanego upośledzenia umysłowego [2-4]. Dzieci z zespołem Downa już od urodzenia pozostają pod opieką specjalistycznych placówek medycznych [5]. Częste występowanie w tym zespole patologii w zakresie układu nerwowego, mięśniowego, kostno-stawowego, wrodzonych wad serca, przewodu pokarmowego oraz układu moczowo-płciowego, rzadziej oddechowego, sprawia, że

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…It has been proven that excessive gene expression increases the risk of cardiovascular diseases, which leads to the impairment of tolerance to physical effort and decreased endurance. Affected individuals are more prone to fatigue and exhibit intolerance of sustained periods of exercise, especially of aerobic exercise [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been proven that excessive gene expression increases the risk of cardiovascular diseases, which leads to the impairment of tolerance to physical effort and decreased endurance. Affected individuals are more prone to fatigue and exhibit intolerance of sustained periods of exercise, especially of aerobic exercise [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…DS is connected with abnormalities of nine genes responsible for the development, functioning, and structure of the nervous system [3]. Research has indicated the existence of dysfunctions in hormone balance, which triggers irregularities in the body's adaptation functions [6].…”
Section: Introductionmentioning
confidence: 99%